Impact of Green Management and Earning Management of Energy Companies in Indonesia - Suripto, Suripto; Hermawan, Dedy; Sari, Putri Irmal; Rifai, Ahmad (International Journal of Energy Economics and Policy, 2022)
This study examines the effect of green management on earnings management in energy companies in Indonesia. The green management variable is proxied by environmental management, environmental performance, and environmental environment by using secondary data. The data used in this study is a regression panel data analysis for the 2015-2019 period. This study finds that green management does not have an impact on earnings management, but the size of the company that determines earnings management. The implication is that energy companies in Indonesia that implement green management do not determine companies to practice earnings management. On the other hand, the practice of earnings management is determined by the size of the company. Large companies tend to practice earnings management in providing financial statement information. Simultaneously, the green management variable and the size of the company together determine the company's earnings management practices in energy companies in Indonesia.